A high-throughput assay for screening natural products that boost NK cell-mediated killing of cancer cells - Zihang Xu; Xiaowen Zhu; Lin Su; Chunpu Zou; Xiao Chen; Yifei Hou; Chenyuan Gong; Wanyi Ng; Zhongya Ni; Lixin Wang; Xuewei Yan; Yangzhuangzhuang Zhu; et al. (Taylor & Francis Group, 2020)
Context Natural killer (NK) cells can eliminate malignant cells and play a vital role in immunosurveillance. Administration of natural compounds represents a promising approach for antitumor immunotherapy, which may enhance the NK cell activity via multiple mechanisms. Objective Establishing approaches to evaluate the effect of select natural products on NK cell-mediated cytotoxicity. Materials and methods We selected a natural product library containing 2880 pure compounds, which was provided by the National Centre for Drug Screening of China. 0.1% DMSO was employed as a negative control, and 100 U/mL human recombinant IL-2 was employed as a positive control. To evaluate the % of tumour cells which were killed by NK cells, expanded NK cells were co-cultured with tumour cells and then treated with natural products at the concentration of 10 μM. After 24-h co-incubation, luminescent signal was detected and percent lysis was calculated. Results We report on the results of a three-round high-throughput screening effort that identified 20-deoxyingenol 3-angelate (DI3A) and its analogue ingenol 3-angelate (I3A) as immuno enhancers which boosts NK cell-mediated killing of non-small cell lung cancer cells (NSCLCs). Biophotonic cytotoxicity assay and calcein release assay were used as two well-established NK cell cytotoxicity detection assays to validate the immuno-enhancing effects of DI3A and I3A, which was achieved by increasing degranulation and interferon-gamma secretion of NK cells. Conclusions Our newly established ATP-based method was a valuable and information-rich screening tool to investigate the biological effects of natural products on both NK cells and tumour cells.